NGHIÊN CỨU LÝ THUYẾT CỦA TƯƠNG TÁC GIỮA CH3COCH3, CH3COCHX2 (X = F, Cl, Br) VỚI HNO BẰNG PHƯƠNG PHÁP HÓA HỌC LƯỢNG TỬ - Thu Trang, Nguyễn Thị; Hiền, Đỗ Thanh; Huế, Trần Thành; Thắng, Nguyễn Văn; Trung, Nguyễn Tiến (Vietnam Journal of Chemistry, 2012)
Obtained binding energies corrected by both ZPE and BSSE range from 10.6 to 14.0 kJ.mol-1 at the level of theory MP2/aug-cc-pVDZ, indicating the existence of stable complexes of interactions between acetone, its halogen-substituted derivatives (CH3COCHX2, with X=F, Cl, Br) and HNO. The significantly blue shift of the N-H bond was achieved in these systems with increase of stretching frequency by about 110 cm-1 as a result of complexation. This is a remarkable observation because the contraction of N-H covalent bond has rarely been detected due to its high polarity. Along with contraction of the N-H bond length, its increment of stretching frequency and decrement of infrared intensity, the stretching frequency blue shift of C-H bond involved in hydrogen bond is also predicted in D1.2. On the other hand, the red shifting hydrogen bonds of C-H×××O type are observed in the remaining complexes D1, D1.3 and D1.4. The obtained results show that the red shift of C-H covalent bond involved in hydrogen bond increases in going from flouride-substituted derivative of acetone (CH3COCHX2) via chlorine one and finally to bromide one, indicating that the more the polarization of C-H bond is the more the red shift of C-H bond is.